Assessing Carnivorous Plants for the Production of Recombinant Proteins - Miguel, Sissi; Nisse, Estelle; Biteau, Flore; Rottloff, Sandy; Mignard, Benoit; Gontier, Eric; Hehn, Alain; Bourgaud, Frédéric (Frontiers in Plant Science, 2019)
The recovery of recombinant proteins from plant tissues is an expensive and time-consuming process involving plant harvesting, tissue extraction, and subsequent protein purification. The downstream process costs can represent up to 80% of the total cost of production. Secretion-based systems of carnivorous plants might solve this problem. Drosera and Nepenthes are able to produce and excrete out of their tissues a digestive fluid containing up to 200 mg. L-1 of natural proteins. Based on the properties of these natural bioreactors, we aimed to develop new plant recombinant protein platforms exhibiting reduced downstream process costs. Original protocols of stable and transient genetic transformation have been set up for both Drosera and Nepenthes sp.. The two major drawbacks concerning the proteases naturally present in the secretions and a polysaccharidic network composing the Drosera glue were overcome by modulating the pH of the plant secretions. At basic pH, digestive enzymes are inactivated and the interactions between the polysaccharidic network and proteins in the case of Drosera are subdued allowing the release of the recombinant proteins. For D. capensis, a concentration of 25µg of GFP/ml of secretion (namely 2% of TSP from glue) has been obtained for stable transformants. For Nepenthes, a concentration of 0,5ng of GFP/ml secretions (namely 0,5% of TSP from secretions), 12ng can be produced by one pitcher in only 14 days for transiently transformed plants. This plant-based expression system shows again the potentiality of biomimetic approaches leading, this time, to a valuable plant factory.